Zapomniany panegiryk Ignacego Srzednickiego ku czci Kazimierza Nestora Sapiehy - Maksimowicz, Krystyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The poem of Ignacy Srzednicki addressed to Kazimierz Nestor Sapieha was created during the Great Sejm, when the addressee served as the Speaker of the Seimas and the General Confederation of the Polish-Lithuanian Commonwealth. The author reconstructs the biography of the creator of the poem, explores the relationship between Srzednicki and Sapieha, as well as analyses and interprets the poem included in the appendix.